Sistem Pendeteksi Hujan Menggunakan Sensor Air Dan Led - Eko Saputra; Nina Paramytha (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The increasing unpredictability of climate change demands a system capable of automatically detecting rainfall and providing early warnings. This study aims to design and develop a rain detection system based on a water sensor and LED using an Arduino Uno microcontroller. The system operates by detecting water presence on the rain sensor and providing a visual indication through an LED. The research methodology follows a Research and Development (R&D) approach, including literature review, hardware and software design, implementation, and system testing. The test results indicate that the system can accurately detect rainfall and respond to weather changes in real-time. This system has the potential to be applied in various sectors, such as agriculture, transportation, and industry, to mitigate risks caused by sudden rain. Further development can integrate Internet of Things (IoT) technology for remote weather monitoring.